Performance Evaluation and Comparative Analysis of Small Solar Panels for IoT Battery Charging Using ESP32 Microcontroller Platform - IzuKhairi Misrawi Rohali; Mohamad Rifa Algifari Mulia Sembiring; Sumaryanto; Ratu Mutiara Siregar; Saddam Husein Siregar (CV. Sakura Digital Nusantara, 2026)
Purpose – Small photovoltaic panels are widely used to support low-cost Internet of Things (IoT) sensor nodes; however, many locally available panels provide only nominal voltage labels without complete electrical specifications. This study evaluates the charging performance of three small solar panel configurations for a single 18650 lithium-ion battery used in an IoT-based monitoring node.Methods – The experimental system used Lolin D32 boards based on ESP32, TP4056 charging modules, and identical battery connections. Node 1 used a large 9 V solar panel connected to a DC-DC step-down module calibrated to 5 V before entering the TP4056 input. Node 2 used a medium 6 V panel, while Node 3 used a mini solar panel directly connected to the charging module. Battery voltage was recorded every five minutes, converted into apparent state of charge (SoC), and uploaded to Google Sheets. The main field test was conducted from 10:00 to 15:00 on 8 June 2026.Findings – Node 1 produced the highest apparent charging performance, with a charging rate of 12.8 percentage points per hour and a total SoC increase of 63.8 percentage points. In contrast, Node 2 and Node 3 each achieved only 0.5 percentage points per hour during the same test period. Research implications – The findings indicate that nominal voltage alone is insufficient for selecting solar panels for IoT battery charging. Panel area, current capability, charger compatibility, firmware measurement sequence, and direct field validation must be considered.Originality – This study provides practical field-based evidence for selecting small photovoltaic panels in low-cost IoT battery charging applications.